Discrete Bimodal Probes for Thrombus Imaging - Uppal, Ritika (2012)
Here we report a generalizable solid/solution phase strategy for the synthesis of discrete bimodal fibrin-targeted imaging probes. A fibrin-specific peptide was conjugated with two distinct imaging reporters at the C- and N-terminus. In vitro studies demonstrated retention of fibrin affinity and specificity. Imaging studies showed that these probes could detect fibrin over a wide range of probe concentrations by optical, magnetic resonance, and positron emission tomography imaging.